Medical Education Curricula in Pakistan Must Address the Consequences of Climate Change on the Health of the People and their Solution - Piryani, Rano Mal; Piryani, Suneel (Journal of Liaquat University of Medical & Health Sciences, 2024)
The World Health Organization (WHO) has documented that "climate change has been intensifying public health problems and described climate change as one of the leading human health threats1. In reality, climate change is now a public health emergency, as evident from the increased incidence of wildfires, extremes of heat waves, increased floods, and shifting patterns of infectious disease2.